LINC00511 exacerbated T-cell acute lymphoblastic leukemia via miR-195-5p/LRRK1 axis - Li, Shengli (Biosci Rep, 2020)
T-cell acute lymphoblastic leukemia (T-ALL) is a malignant disease arising from the abnormal proliferation of T lymphocyte in marrow. Long non-coding RNAs (lncRNAs) are one kind of non-coding RNAs (ncRNAs), which were reported to modulate the initiation or progression of diverse cancers. However, the role of LINC00511 in T-ALL was unknown. To figure out the function and mechanism of LINC00511 in T-ALL, a series of experiments were carried out. Based on the experimental results, we discovered that LINC00511 boosted cell proliferation and invasion, but hindered cell apoptosis in T-ALL cells. Besides, based on bio-informatics tool, miR-195-5p was selected for further exploration. Then, miR-195-5p was validated to bind with LINC00511. Hereafter, LRRK1 was testified to serve as a target gene of miR-195-5p. At last, rescue assays suggested that LRRK1 overexpression restored sh-LINC00511#1-mediated effects on cell proliferation and apoptosis. All in all, LINC00511 exacerbated T-ALL progression via miR-195-5p/LRRK1 axis, implying a potential therapeutic clue for the patients with T-ALL.